Identity and discourse in young teenagers of the Colegio Universidad Cooperativa de Colombia - Gómez Palacio, Germán David; Carrasco Tapias, Nayib (Pensando Psicología, 2013)
This research, carried out at the Faculty of Psychology of the Universidad Cooperativa de Colombia between 2009 and 2010 by the “Education and development” research group, studies how discourse affects the identity of the youths from the Colegio Universidad Cooperativa de Colombia in the Corregimiento of San Antonio de Prado in the municipality of Medellín. In order to explain identity we start from the theoretical considerations that consider it a dynamic process, rather than a static one, thus challenging the traditional conceptions of human development through unmodifiable stages. In this work we propose a dialectic perspective in which particular and social aspects of the subject come together. This allows the appearance of new aesthetic and narrative forms of identity that are subject to the changes and times science proposes.
Keywords: adolescence; discourse; identity; social interaction; subjectivation